Potencial do teste de emergência em canteiro para estimar o estabelecimento da cultura do milho no campo - Silva, Flávia Andrea Nery (2012)
High physiological quality seed lots indicate that, probably, there will be good performance under several field conditions, and the reference to evaluate this quality is the germination test in the laboratory, which is done under optimal conditions to express all the seed potential. However, laboratory results do not always repeat in the field, where conditions of the seed bed are not ideal to express the same germination. The emergence test in seed bed can aid in obtaining more reliable information about the performance of seed lots. Therefore, this study evaluated the efficacy of field emergence test to confirm the physiological performance of maize seeds, under different soil conditions, with or without water deficit. Four experiments were done, consisting in the combination of two soil types, very clayey or medium texture, and two hydric regimens (with or without restriction). The experimental design was randomized blocks, with three repetitions, for all experiments. The treatments were distributed as a 3x4 factorial. The first factor consisted of three seed lots with different vigor levels (high, medium and marginal vigor) and the second factor of four sowing depths (2, 4, 6 and 8 cm). Daily readings of seedling emergence were done until stabilization of emergence. The following variables were calculated with the data collected: Emergence (E), Index of emergence velocity (IVE), Index of field emergence (IEC), Average time for emergence ( ), Average emergence velocity ( ), Coefficient of variation of time (CVt), Index of emergence synchrony (Z), Uncertainty (I) and Relative frequency of emergence (Fr). The data were compared individually for each soil texture and its hydric regimen, and by grouped analysis, comparing the effects of soil textures, and the effects of water restriction in the soil textures. It can be concluded that: a) the variations in soil texture, sowing depth, and hydric regimen affected the performance of maize seeds distinctly as a function of vigor level, b) the interactions among the factors studied and the levels are conclusive proof that the use of field emergence test is equivocated for the validation of vigor tests in the laboratory, and c) unusual seedling emergence measures in the field, such as those used in this study, are important tools to describe the emergence process of maize seedlings.